Decision making for the central compartment in differentiated thyroid cancer. Issue 11 (November 2018) - Gonçalves Filho, João; Zafereo, Mark E.; Ahmad, Faisal I.; Nixon, Iain J.; Shaha, Ashok R.; Vander Poorten, Vincent; Sanabria, Alvaro; Hefetz, Avi Khafif; Robbins, K. Thomas; Kamani, Dipti; Randolph, Gregory W.; Coca-Pelaz, Andres; et al.
Abstract: The central compartment is a common site for nodal spread from differentiated thyroid carcinoma, often occurring in patients without clinical or ultrasonographic (US) evidence of neck lymph node metastasis (cN0). However, the role of elective central compartment neck dissection (CND) among patients with DTC remains controversial. We performed a systematic literature review, also including review of international guidelines, with discussion of anatomic and technical aspects, as well as risks and benefits of performing elective CND. The recent literature does not uniformly support or refute elective CND in patients with DTC, and therefore an individualized approach is warranted which considers individual surgeon experience, including individual recurrence and complication rates. Patients (especially older males) with large tumors (>4 cm) and extrathyroidal extension are more likely to benefit from elective CND, but elective CND also increases risk for hypoparathyroidism and recurrent nerve injury, especially when operated by low-volume surgeons. Individual surgeons who perform elective CND must ensure the number of central compartment dissections needed to prevent one recurrence (number needed to treat) is not disproportionate to their individual number of central compartment dissections per related complication (number needed to harm).